THE INFLUENCE OF HEALTH EDUCATION ABOUT NUTRITION IN THE ELDERLY ON BODY WEIGHT IN THE MEDAN AREA PUSKESMAS - Triana, Heni Triana; Khoirun Nisa Nst (Mitra Husada Health Internasional Conference (MIHHICo), 2024)
Monitoring nutritional status is related to regular body weight weighing at least once a week, be aware of weight gain or weight loss of more than 0.5 kg/week. An increase in weight of more than 0.5 kg in 1 week is a risk of being overweight and a weight loss of more than 0.5 kg / week indicates being underweight The general aim of the research is to analyze the effect of health education on nutrition for the elderly on body weight at the Medan Area Health Center. This type of research is quantitative using a quasi-experimental design, a group design without a control group using the method (one group pre test and post test design). The total sampling technique was 65 people. The research results showed that the description of knowledge before Health Education Using Posters about nutrition at the Medan Area Health Center was found to be less than 44 people (67.79%) and after Health Education Using Posters about nutrition at the Medan Area Health Center it was found to have increased to the good category of 54 people (83.1%). The Influence of Education Health Using Using Posters about nutrition at the Medan Area Community Health Center was found to have an influence with a p value of 0.000 and t-test 20.121 and the Effect of Health Education Using Using Posters about nutrition on body weight at the Medan Area Community Health Center was found to have an influence with a p value of 0.000 and t-test 10.732 For the elderly, they can apply the information they have obtained to consume food according to nutritional standards. For the Community Health Center, carry out regular outreach programs at the Community Health Center in the education program about nutrition for the elderly at the Community Health Center.